IMPLEMENTASI KEBIJAKAN SURVEI KEPUASAN PELAYANAN PUBLIK PADA LEMBAGA REHABILITASI NARKOBA: STUDI KASUS DI KOTA PEKANBARU - Mariana Mariana; Yeni Triana; Irawan Harahap (Jurnal Ilmiah Advokasi, 2025)
Public dissatisfaction with the quality of public services at drug rehabilitation institutions in Pekanbaru City has shown an increasing trend, even leading to the closure of several rehabilitation centers. This condition highlights the importance of the Community Satisfaction Survey (CSS) as an evaluative instrument to improve the quality of public services. This study aims to analyze the implementation of the Community Satisfaction Survey policy based on Regulation of the Minister of Administrative and Bureaucratic Reform Number 14 of 2017, to identify obstacles to its implementation, and to examine the efforts undertaken by drug rehabilitation institutions in Pekanbaru City. This research employs a sociological legal research method with an empirical approach, utilizing primary, secondary, and tertiary data collected through interviews, document analysis, and literature review. The findings indicate that the implementation of the CSS policy has not been optimal, as several rehabilitation institutions have not consistently conducted community satisfaction surveys. The main obstacles include low legal awareness among institutional administrators, limited budget allocation, and insufficient human resource competence in conducting surveys. Furthermore, some institutions have not taken concrete and systematic measures to implement the policy. Therefore, this study recommends strengthening the government’s role through guidance, supervision, and the imposition of administrative sanctions, such as written warnings and fines, to ensure compliance of drug rehabilitation institutions with the public service satisfaction survey policy. Keywords: drug rehabilitation; public services; community satisfaction survey; policy implementation.